2016
DOI: 10.1039/c5ra25859f
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-based preparation and luminescence studies of SiO2 fibers doping Eu3+ activator in interstitial sites

Abstract: The formation mechanism of SiO2:Eu3+ fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…2 27 In addition, by comparing the FT-IR spectra of NAS and NAS:Eu 3+ samples, it can be seen that the FT-IR spectra of NAS:Eu 3+ samples exhibit a significant peak of Si-O-Eu covalent bonds at 1408 cm À1 . 22,29,30 This phenomenon indicates that the doped Eu 3+ ions have occupied the lattice of Na + ions, which is consistent with the XRD analysis shown in part 3.1.…”
Section: The Charge Compensation Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…2 27 In addition, by comparing the FT-IR spectra of NAS and NAS:Eu 3+ samples, it can be seen that the FT-IR spectra of NAS:Eu 3+ samples exhibit a significant peak of Si-O-Eu covalent bonds at 1408 cm À1 . 22,29,30 This phenomenon indicates that the doped Eu 3+ ions have occupied the lattice of Na + ions, which is consistent with the XRD analysis shown in part 3.1.…”
Section: The Charge Compensation Analysissupporting
confidence: 86%
“…Furthermore, the presence of expected elements such as Na, Al, Si, O, Eu, and Bi in the NAS and NAS:1% Bi 3+ ,2%Eu 3+ products was proved from the mapping of each element and it also can be clearly observed that all the elements were evenly distributed in the NAS and NAS:1%Bi 3+ ,2%Eu 3+ samples. 22 In addition, the mass ratio of each element in the NAS and NAS:1%Bi 3+ ,2%Eu 3+ samples were shown in Table 4, which were similar to the standard values. These results also proved that the synthetic samples were pure phase consisting with the result of XRD.…”
Section: Phase Analysissupporting
confidence: 72%
See 1 more Smart Citation
“…The weight loss observed at around 500 °C and the exothermic peak at this temperature were associated with the combustion of PVP carbonaceous residue. PVP degraded basically in two stages: one between 220 and 430 °C related with the degradation of the side chain of PVP, and other between 450 and 550 °C resulted from the oxidation and decomposition of polymer residues [18][19][20][21][22][23]. Moreover, above 550 °C mass losses did not occur and only the polymorphic alumina transformations took place.…”
Section: Resultsmentioning
confidence: 99%
“…The third stage in the temperature changed from 344 ℃ to 414 ℃ accompanied by a small exothermic peak near 407 ℃ in the DTA curve, corresponding to 23.77% weight loss, which associated with the further degradation of polymer residues such as the main chain of PVP. 22 The fourth stage in the temperature changed from 414 ℃ to 581 ℃ , corresponding to 8.96% weight loss, which associated with the crystallization of Lu2O3. 23,24 Above 600 ℃, no further weight loss and thermal events were observed in the corresponding TG-DTA curves, which indicated that water and all organic compounds in composite fibers were removed completely and pure Eu 3+ doped Lu2O3 fibers were obtained.…”
Section: Sample Characterizationmentioning
confidence: 92%